Performing arithmetic operations over the (L–R)-type fuzzy numbers - Raskin, Lev; Sira, Oksana (Technology center PC, 2020)
The issue of constructing a system of rules to perform binary operations over fuzzy numbers has been formulated and considered. The set problem has been solved regarding the (L–R)-type fuzzy numbers with a compact carrier. Such a problem statement is predetermined by the simplicity of the analytical notation of these numbers, thereby making it possible to unambiguously set a fuzzy number by a set of values of its parameters. This makes it possible, as regards the (L–R)-type numbers, to reduce the desired execution rules for fuzzy numbers to the rules for simple arithmetic operations over their parameters. It has been established that many cited works provide ratios that describe the rules for performing operations over the (L–R)-type fuzzy numbers that contain errors. In addition, there is no justification for these rules in all cases. In order to build a correct system of fuzzy arithmetic rules, a set of metarules has been proposed, which determine the principles of construction and the structure of rules for operation execution. Using this set of metarules has enabled the development and description of the system of rules for performing basic arithmetic operations (addition, subtraction, multiplication, division). In this case, different rules are given for the multiplication and division rules, depending on the position of the number carriers involved in the operation, relative to zero. The proposed rule system makes it possible to correctly solve many practical problems whose raw data are not clearly defined. This system of rules for fuzzy numbers with a compact carrier has been expanded to the case involving a non-finite carrier. The relevant approach has been implemented by a two-step procedure. The advantages and drawbacks of this approach have been identified.

Сформульовано і розглянуто проблему формування системи правил виконання бінарних операцій над нечіткими числами. Поставлену задачу розв’язано з нечіткими числах (L–R)–типу з компактним носієм. Така постановка задачі обумовлена простотою аналітичного опису цих чисел, що дозволяє однозначно задати нечітке число набором значень його параметрів. Ця обставина стосовно до чисел (L–R)–типу дає можливість звести шукані правила виконання операцій над нечіткими числами до правил виконання простих арифметичних операцій над їх параметрами. Встановлено, що у великій кількості цитованих робіт наводяться співвідношення, що описують правила виконання операцій над нечіткими числами (L–R)–типу, які містять помилки. Крім того, у всіх випадках відсутнє обґрунтування цих правил. З метою побудови коректної системи правил нечіткої арифметики запропоновано сукупність метаправил, що визначають принципи побудови та структуру правил виконання операцій. З використанням цієї сукупності метаправил розроблено і описано систему правил виконання основних арифметичних операцій (додавання, віднімання, множення, ділення). При цьому для правил множення і ділення наведені різні правила залежно від положення носіїв чисел, що беруть участь в операції, по відношенню до нуля. Запропонована система правил забезпечує можливість коректного розв’язання безлічі практичних задач, в яких вихідні дані визначені нечітко. Ця система правил над нечіткими числами з компактним носієм поширена випадок з нескінченним носієм. Відповідний підхід реалізується двокроковою процедурою. Визначено переваги та недоліки цього підходу.
Виконання арифметичних операцій над нечіткими числами (L–R)–типу
Keywords: (L–R)-type fuzzy numbers; compact carrier; rules for performing arithmetic operations; нечіткі числа (L–R)–типу; компактний носій; правила виконання арифметичних операцій